Comparative Outer Membrane Protein Analysis of High and Low-Invasive Strains of Cronobacter malonaticus - Aldubyan, Maha A.; Almami, Ibtesam S.; Benslimane, Fatiha M.; Alsonosi, Abdlrhman M.; Forsythe, Stephen J. (Frontiers in Microbiology, 2017)
Cronobacter are an important group of foodborne pathogens that has been linked to life-threatening infections in both infants and adults. The major infections associated with Cronobacter species are neonatal meningitis, necrotizing enterocolitis and septicaemia. There are seven species in the Cronobacter genus, of which only three are of clinical importance; C. sakazakii, C. malonaticus and C. turicensis. To date most studies have focussed on C. sakazakii as it is the major species associated with neonatal infections. However recently C. malonaticus, in particular sequence type 7 (ST7), has been noted as being prevalent in adult infections and therefore warranting further investigation. In this study, eight strains of C. malonaticus ST7, that had been isolated from a wide range of sources and varied in their in vitro virulence, were chosen for proteomic analysis of their outer membrane proteins (OMPs). 1D gel analysis revealed a ~29 kDa size band that was only present in the highly invasive strains. Subsequent mass spectrometric analysis identified several peptides that matched the flagellin protein. The presence of flagellin protein was confirmed in 2D gel spot. Mass spectrometry analysis of total OMPs revealed that the four highly invasive C. malonaticus strains expressed the main flagellum proteins that were absent from the four low invasive strains. These were the flagellar hook protein FlgE, flagellar hook-associated protein 1, flagellar hook-associated protein, flagellin and flagellar hook-filament junction protein FlgL. This data indicates that C. malonaticus flagellar proteins may have an important role in the organism’s invasion properties.